Valores de referência e equação preditora para o teste de caminhada de seis minutos em crianças saudáveis de 7 a 12 anos no Brasil: estudo TC6minBRASIL - Cacau, Lucas de Assis Pereira (2017)
Introduction: Brazil is a country with great climatic, socioeconomic and cultural differences that still does not have a reference value for the six-minute walk test in healthy children. In order to avoid misinterpretations, the use of equations to predict the maximum distance traveled must be established in each country. Objectives: To establish reference values for 6MWT in healthy children aged 7 to 12 years in Brazil; Determine the variables that influence the distance traveled; elaborate an equation to predict the maximum distance traveled and test this equation to predict the maximum distance traveled in 6MWT in an independent sample of healthy children aged 7 to 12 years in Brazil. Methods: The study enrolled 1496 healthy children, evaluated by 11 centers in all regions of Brazil, aged 7 to 12 years, recruited in public and private schools in their respective regions. The steering committee of the study TC6minBrasil held a videoconference with each center to present the study, guidelines on the organization of the physical space and application of the test. After the inclusion of the child in the study, the data were collected and inserted into standardized charts. Each child was weighed on a scale and measured with tape measure to obtain the values of weight and height. Heart rate and peripheral oxygen saturation (%) and blood pressure (mmHg) were checked and recorded on the evaluation card. The main outcome of the study was the distance walked through the six-minute walk test. The statistical program R was used to analyze the data. Results: There was Gaussian behavior of the sample in relation to the distance covered in the Tc6min. The mean distance traveled in males (531.1 m) and the difference of 24.9 m (p <0.0001) in females (506.2 m) was also observed. Reference values were set for 6MWT and the following equations were calculated to predict the distance traveled for males: Distance = 16.86 * Age + 1.89 * HrDelta-0.80 * Weight + 336.91GR1 + 360.91GR2 and for females: Distance = 13.54 * Age + 1.62 * Hr Delta-1.28 * Weight + 352.33GR1 + 394.81GR2. Conclusion: Reference values for Tc6min were established in healthy children aged 7 to 12 years in Brazil and equations were generated to predict the maximum distance covered in Tc6min. In addition, the equation established in this study was able to predict the maximum distance traveled, with errors of approximately 10 meters on average, when tested in an independent sample.